2022
DOI: 10.1002/cam4.4499
|View full text |Cite
|
Sign up to set email alerts
|

Midlife brain metastases in the United States: Is male at risk?

Abstract: Background Population‐based estimates of the impact of gender throughout the whole course of brain metastases (BMs) at the time of diagnosis of systemic malignancies are insufficient. We aimed to discover the influence of gender on the presence of BMs in newly diagnosed malignancies and the survival of those patients on a population‐based level. Methods Midlife patients (40 years ≤ age ≤60 years) with newly diagnosed malignancies and BMs at the time of diagnosis were abstracted from the Surveillance, Epidemiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that in addition to surgery, gender, race, adenocarcinoma, marital status, insurance status, mediastinal lymph nodes and other factors are also related to the prognosis of NSCLC patients with BM (19,(23)(24)(25)(26)(27)(28). It has also been reported (22,29) that the prognosis of lung surgery in NSCLC patients with BM is not related to mediastinal lymph node stage and T stage of lung lesions (11,22).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that in addition to surgery, gender, race, adenocarcinoma, marital status, insurance status, mediastinal lymph nodes and other factors are also related to the prognosis of NSCLC patients with BM (19,(23)(24)(25)(26)(27)(28). It has also been reported (22,29) that the prognosis of lung surgery in NSCLC patients with BM is not related to mediastinal lymph node stage and T stage of lung lesions (11,22).…”
Section: Discussionmentioning
confidence: 94%
“…However, the actual prevalence may be higher, as these estimates are typically restricted to individuals who are being evaluated for therapy. According to a study presented by Che [ 32 ], most BMs metastasize from lung cancer (40–50%), breast cancer (15–25%), and melanoma (5–20%). However, cancer patients with BMs continue to have a poor prognosis, with a relatively low median survival (2.9 months for newly diagnosed malignancies) and 2-year survival rate (8%).…”
Section: Resultsmentioning
confidence: 99%
“…The SEER program suggests arenas for future epidemiological studies of SBMs, which were hardly going forward to determine the exact incidence before 2016, since reporting BMs was not mandated by local and federal registries [ 18 ]. As mentioned in the literature review, 2.03% of all solid cancer patients and 2.08% of midlife patients had synchronous BMs [ 11 , 12 ]. Lung cancer SBMs, breast cancer SBMs, renal cancer SBMs, melanoma SBMs, and colorectal cancer SBMs ranked as the top five in terms of the number of patients in the entire cohort [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…For patients diagnosed with systemic malignant malignancy between 2010 and 2013, information on synchronous brain metastases at the time of primary tumor diagnosis was first available in 2016 [ 11 , 12 , 13 ]. The ten-year (2010–2019) accessible information on synchronous brain metastases (SBMs) better reflected the change in the epidemic pattern over the research period when the analyses were updated to incorporate more recent data released in April 2022 based on the November 2021 submission.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation